DG Optimization in Power Systems Considering Power Losses and CB Rating Violations - Akin, Firat; Dinc, Murat; Arikan, Oktay (IEEE, 2025)
One of the main challenges of increasing distributed generation (DG) penetration in power systems is the rise in fault current levels. This study presents a DG optimization approach for the IEEE 118-bus system with 19 generators, considering the violation of circuit breaker (CB) ratings due to fault current increases. The proposed method determines the optimal number, location, and size of DG units while minimizing active power losses and applying a penalty for CB rating violations. The optimization problem is solved using three well-known metaheuristic algorithms: Grey Wolf Optimizer (GWO), Genetic Algorithm (GA), and Particle Swarm Optimization (PSO), implemented in MATLAB. The results show that the proposed approach can effectively manage fault current levels while improving system efficiency through optimal DG placement.
Keywords: Distributed generations; meta-heuristic; 3-phase fault current; CB rating; power loss minimization; DISTRIBUTED GENERATION ALLOCATION; FAULT CURRENT LIMITERS; SHORT-CIRCUIT CURRENT; PROTECTION SYSTEMS; Energy & Fuels; Engineering; Telecommunications